ARTICLE SUMMARIES. (Computer (00189162), 2008)
Abstracts are presented for several articles including "ICT4D 2.0: The Next Phase of Applying ICT for International Development" by Richard Heeks, "Toward Empowered Design" by Gary Marsden, and "Grand Research Challenges in Computer Science in Brazil" by Claudia Bauzer Medeiros.